Enhancing Vocabulary Performance Through Mobile Assisted Language Learning at a Rural School in Indonesia - Katemba, Caroline Victorine (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2021)
Living in this era of globalization and in the 4.0 industrial revolution, we cannot get away from technology because it has integrated into our lives and has penetrated the educational system. There were studies done on the use of mobile-assisted language learning (MALL) to improve students’ vocabulary achievement in other parts of the world and also in some urban schools in Indonesia, but this study seeks to find whether the students’ vocabulary improved through the use of MALL at rural school in Bandung- Indonesia. This study was carried out to find the enhancement of using MALL in vocabulary teaching to 79 grade 8 students in Bandung. This study was designed for quantitative and experimental research. The students were separated into two groups, experimental and control groups. A day before coming to class, 15-20 words to learn the following day was sent to the experimental group through a short messages system (SMS) for them to read, find the synonyms and meanings of those words before coming to the class.   The result of the study showed that students in the experimental group performed better than the control group. It also proves that technology makes a significant difference in the learning of vocabulary in school.